2016
DOI: 10.1007/s00270-016-1389-z
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous Image-Guided Screw Fixation of Bone Lesions in Cancer Patients: Double-Centre Analysis of Outcomes including Local Evolution of the Treated Focus

Abstract: PIGSF is feasible for a wide range of oncologic patients, offering good short-term efficacy, acceptable complication rates, and rapid recovery. Unfavourable local evolution at imaging may be relatively frequent, and requires close clinico-radiological surveillance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(30 citation statements)
references
References 41 publications
0
30
0
Order By: Relevance
“…In a series of 36 pelvic bone and proximal femur metastases, Cazzato et al reported pain and functional improvement in 87.1% of cases. 30 Three patients had unfavorable outcome because of insufficient consolidation (n ¼ 1) or secondary screw displacement (n ¼ 2).…”
Section: Percutaneous Screw Fixationmentioning
confidence: 99%
See 1 more Smart Citation
“…In a series of 36 pelvic bone and proximal femur metastases, Cazzato et al reported pain and functional improvement in 87.1% of cases. 30 Three patients had unfavorable outcome because of insufficient consolidation (n ¼ 1) or secondary screw displacement (n ¼ 2).…”
Section: Percutaneous Screw Fixationmentioning
confidence: 99%
“…Thanks to the improvements of image guidance, screw fixation with minimally invasive interventional radiology approach has recently emerged. 30,31 Navigation softwares integrated with computed tomography (CT) or cone beam CT allow precise screw insertion, even if bone landmarks are altered by tumor destruction. If needed, screw fixation can easily be combined with cementoplasty to achieve optimal anchorage and to avoid secondary screw displacement.…”
Section: Percutaneous Screw Fixationmentioning
confidence: 99%
“…In cases of failure, having maintained a close collaboration with orthopaedic surgery colleagues throughout the patient's care will facilitate a multidisciplinary discussion of appropriate treatment options going forward, as major surgical fixation or additional osteoplasty may be required (►Fig. 8).…”
Section: Complication Managementmentioning
confidence: 99%
“…Therefore, patients presenting with pelvic metastases causing instability, especially when symptomatic, can greatly benefit from minimally invasive stabilization techniques that provide pain relief, maintain mobility, and essentially remove significant delays or interruptions in critical systemic therapies. [6][7][8][9][10][11] Herein, we describe some of the clinical and technical considerations of our pelvic "screw and glue" technique developed in close collaboration between our interventional radiology and orthopaedic oncology services and performed in over 120 patients over the past decade.…”
mentioning
confidence: 99%
“…30 Percutaneous screw fixation describes the minimally invasive placement of metallic screws across pathologic lesions in weight-bearing osseous structures. [31][32][33] Percutaneous screw fixation may be performed with either CT or fluoroscopic guidance. Optimal imaging utilization depends on lesional characteristics and screw trajectory.…”
Section: Msk Ir Treatment Techniquesmentioning
confidence: 99%